2014
DOI: 10.1016/j.oraloncology.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Oral health, dental care and mouthwash associated with upper aerodigestive tract cancer risk in Europe: The ARCAGE study

Abstract: Objective: To evaluate the association of oral health (OH), dental care (DC) and mouthwash with tumors of the upper-aerodigestive tract (UADT), and to which extend enzymes involved in the metabolism of alcohol modify the effect of alcohol-based mouthwashes.' Materials and Methods: Subjects were interviewed about OH and DC behaviors. Mouthwash use was analyzed in relation to alcohol dehydrogenase genes (ADH1B,ADH1C,ADH7) and one aldehyde dehydrogenase gene (ALDH2) known to be associated with head and neck cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(122 citation statements)
references
References 50 publications
4
115
0
3
Order By: Relevance
“…In conclusion, the results of this pooled analysis confirm recent systematic reviews and meta-analyses [3, 20] and multicenter studies [21] that reported no overall increased risk of head and neck cancer in individuals who ever used mouthwash, but an association in long-term frequent users. The study is limited by significant methodological issues, yet reveals potential risks for head and neck cancer sub-sites and in long-term and frequent users of mouthwash.…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, the results of this pooled analysis confirm recent systematic reviews and meta-analyses [3, 20] and multicenter studies [21] that reported no overall increased risk of head and neck cancer in individuals who ever used mouthwash, but an association in long-term frequent users. The study is limited by significant methodological issues, yet reveals potential risks for head and neck cancer sub-sites and in long-term and frequent users of mouthwash.…”
Section: Discussionsupporting
confidence: 89%
“…However, it remains uncertain whether the consumption of alcohol and tobacco, in addition to individual parameters modify the normal process of epithelial maturation of the oral cavity. Other factors that may change the pattern of oral epithelial maturation are oral hygiene status and socioeconomic factors, since they have been suggested as risk factors for the development of oral cancer [8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral health is reportedly a risk factor for upper aerodigestive tract tumors, including tumors of the oral cavity, larynx, oropharynx, hypopharynx and esophagus [10][11][12][13] . This risk is independent of tobacco use and alcohol consumption [13] .…”
Section: Introductionmentioning
confidence: 99%